Mathematical Models Arising in the Fractal Forest Gap via Local Fractional Calculus - Chun-Ying Long; Yang Zhao; Hossein Jafari (Abstract and Applied Analysis)
The forest new gap models via local fractional calculus are investigated. The JABOWA and FORSKA models are extended to deal with the growth of individual trees defined on Cantor sets. The local fractional growth equations with local fractional derivative and difference are discussed. Our results are first attempted to show the key roles for the nondifferentiable growth of individual trees.